Development of Interactive Video as Learning Media to Teach English Speaking Skills for High School Students - Khoirina, Vita; Makrifah, Istina Atul; Saifudin, Ahmad (PROJECT (Professional Journal of English Education), 2025)
This study aims to develop and evaluate an interactive video as a learning media to teach students' English-speaking skills. The research follows the Research and Development (R&D) with ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. In the analysis stage, classroom observations and student questionnaires were conducted to identify learning needs. Based on the findings, the design stage involved determining the appropriate interactive video content, creating scripts, and structuring the video. The development stage included video editing using CapCut, followed by expert validation. The results showed high validity scores: instrument validation (92.5%), media validation (87.5%), and material validation (92.5%), all categorized as "very valid." During implementation, pretests and post-tests were conducted, revealing a 10% increase in students' speaking performance, demonstrating the effectiveness of the interactive video. Finally, in the evaluation stage, a student satisfaction questionnaire resulted in an 80% score, categorized as "very feasible." These findings indicate that the developed interactive video is a valid, feasible, and effective tool for improving students' English-speaking skills.